ANALYSIS OF FACTORS AFFECTING GENERAL SUPPLIERS TO SELL FFB WITH A AND B QUALITY TO PT. SANDABI INDAH LESTARI AND RISK ANALYSIS OF THE RESOURCES - Ali Setia Iskandar; Yuwana Yuwana; Bambang Sumantri (Badan Penerbitan Fakultas Pertanian (BPFP), 2019)
This study studies to analyze the factors that influence general suppliers to choose FFB (Fresh Fruit Bunches) on quality and quality B and calculate the business expenses to be received. This research was conducted in the period August - September 2018 at PT. Sandabi Indah Lestari (SIL). The analytical tool used in this study is multiple linear regression analysis and risk analysis. Based on the results of the analysis, the factors that influence general suppliers choose to sell FFB at quality A and quality B at PT. SIL is the average factor of the weight of FFB supplied, the weight of FFB sorted, the distance to the plant and transportation costs, while the factors that do not significantly affect the long period of receiving FFB at the plant then for the risks received are known that the risk of selling FFB quality A is greater because of loss while FFB that sells quality B is smaller because it avoids losses.Keyword: Suppliers, FFB (Fresh Fruit Bunches), quality A and B, risk